Decision Support System for Determining Exemplary Employees Using the Evaluation Method based on Distance from Average Solution (EDAS) - Adhie Thyo Priandika; Agung Deni Wahyudi (Jurnal Ilmiah Computer Science, 2022)
The selection of the best employees is a critical process in human resource management (HRM) that aims to get individuals who best fit the needs and goals of the organization. This study aims to determine the best employees using Evaluation based on Distance from Average Solution (EDAS) using criteria of Loyalty, Discipline, Liveliness, Responsibilities, Leadership, Organization, Knowledge so that the resulting solution can provide recommendations for decision makers in making a decision. Based on the process of completing steps from stage 1 to stage 7, the selection of the best employees using the Evaluation Method based on Distance from Average Solution (EDAS) resulted in the best employee recommendations obtained on behalf of Yuni with a value of 0.686 to rank 1. 2nd place was obtained by Yustian with a value of 0.566, 3rd place was obtained by Lisa with a value of 0.563, and 4th place was obtained by Andi with a value of 0.486